Diversity and Structure of Demersal Fish Community Over the Northern Slope in the South China Sea - Zhang, Jun; Zhang, Kui; Jiang, Yan-e; Li, Yuan-jie; Fan, Jiang-tao; Yu, Wen-ming; Chen, Zuo-zhi (Frontiers in Marine Science, 2022)
Three bottom trawl surveys over the northern continental slope in the South China Sea (18°50′–20°40′N, 112°50′–115°10′E) were carried out, in June 2015, March 2017 and September 2018, to investigate species composition, biodiversity and community structure of demersal fish. Surveys in 2015, 2017 and 2018 captured 97 fish species (representing 77 genera, 52 families, 26 orders), 108 fish species (representing 84 genera, 61 families, 19 orders) and 126 fish species (representing 105 genera, 74 families, 25 orders), respectively. Three surveys captured a total of 252 fish species, representing 164 genera, 97 families, 30 orders. Perciformes dominated. Species richness in station linking shallow continental shelf with deep slope was the lowest among stations. In three surveys, 16 species occurred in the catches of three surveys, accounting for 6.35% of all species. Species replacement rate between stations showed a significant linear relationship with the depth difference and latitude difference. Margalef’s species richness index (D), Shannon–Weiner diversity index (H’) and Pielou’s evenness index (J’) among stations ranged 2.65–6.74, 1.02–4.15 and 0.28–1.14, respectively. Differences of D, H’ and J’ were insignificant among seasons. There were significant positive linear relations between H’ and J’ and latitude. D, H’ and J’ decreased with increasing sampling depth, however the relations were not significant. Based on multivariate statistical analysis, fish community at species level was divided into five groups with average dissimilarities of 95.69%–99.96%. In terms of genus and family, average dissimilarities among groups were more than 88.11% and 82.69%. There were significant differences in species composition between depths, but no significant differences between seasons and temperatures, as well as in genus and family composition.